ANALISIS FAKTOR TINGKAT KECEMASAN, MOTIVASI DAN PRESTASI BELAJAR MAHASISWA - Sri Adi Widodo; Laelasari Laelasari; Ryky Mandar Sari; Ian Rosita Dewi Nur; Flora Grace Putrianti (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2017)
The purpose of this study was to determine the relationship between the level of anxiety and learning motivation on student achievement. This research is a kind of ex post facto, a six-month study period. A population of 125 students, with a sample of 100 students were randomly selected. The research variables are student achievement as the dependent variable, while the independent variable is the level of anxiety of students and student learning motivation. Data collection methods used were the questionnaire method and documentation. Data analysis technique used is path analysis. It can be concluded that there is a negative relationship between anxiety level of students' motivation, there is no direct relationship between the level of anxiety of students on student achievement through student learning motivation, there is a positive relationship between learning motivation on student achievement. So it can be stated that there is a correlation between the level of anxiety and learning motivation of students simultaneously on student achievement.